The Accumulation of miRNAs Differentially Modulated by Drought Stress Is Affected by Grafting in Grapevine. Issue 4 (24th February 2017) - Pagliarani, Chiara; Vitali, Marco; Ferrero, Manuela; Vitulo, Nicola; Incarbone, Marco; Lovisolo, Claudio; Valle, Giorgio; Schubert, Andrea
Abstract : The abundance of drought-regulated miRNAs is affected by grafting in grapevine. Abstract: Grapevine ( Vitis vinifera ) is routinely grafted, and rootstocks inducing drought tolerance represent a source for adapting vineyards to climate change in temperate areas. Our goal was to investigate drought stress effects on microRNA (miRNA ) abundance in a drought-resistant grapevine rootstock, M4 ( Vitis vinifera × Vitis berlandieri ), compared with a commercial cultivar, Cabernet Sauvignon, using their autografts and reciprocal grafts. RNA extracted from roots and leaves of droughted and irrigated plants of different graft combinations was used to prepare cDNA libraries for small RNA sequencing and to analyze miRNA s by quantitative real-time polymerase chain reaction (RT-qPCR ). Measurements of leaf water potential, leaf gas exchange, and root hydraulic conductance attested that, under irrigation, M4 reduced water loss in comparison with cultivar Cabernet Sauvignon mostly through nonhydraulic, root-specific mechanisms. Under drought, stomatal conductance decreased at similar levels in the two genotypes. Small RNA sequencing allowed the identification of 70 conserved miRNA s and the prediction of 28 novel miRNA s. Different accumulation trends of miRNA s, observed upon drought and in different genotypes and organs, were confirmed by RT-qPCR . Corresponding target transcripts, predicted in silico and validated by RT-qPCR, often showed opposite expression profiles than the related miRNA s. Drought effects on miRNA abundance differed between the two genotypes. Furthermore, the concentration of drought-responsive miRNA s in each genotype was affected by reciprocal grafting, suggesting either the movement of signals inducing miRNA expression in the graft partner or, possibly, miRNA transport between scion and rootstock. These results open new perspectives in the selection of rootstocks for improving grapevine adaptation to drought.